POTENSI PERTUNJUKAN SILEK PANGIAN SEBAGAI ATRAKSI WISATA DI KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Sari, Selvi Gustia; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research discusses the potential of Silek Pangian cultural performances to result in efforts to preserve Silek Pangian. The research method used in this research is a qualitative research method. The movements in silek pangian are the pitupang, steps, tangkok, attack and sambuik movements, these movements are characteristic of silek pangian. Apart from the movement elements, in the Silek Pangian performance the musical instruments used are the traditional musical instruments of the Kuantan singing area, namely the calempong and gondang, the costume elements are also influential, namely wearing all black clothes, wearing a skullcap and cloth as a songket. Supporting elements such as property are important in the silek pangian performance, while using property elements such as swords and shields. In terms of the stage or place where silek pangian is performed, it is in the open air which has been prepared by the silek pangian administrators and the audience who witness silek pangian are from the local community. Keywords: Potential, Performances, Attractions, Tourism, Preservation.